Nanocomplexes derived from chitosan and whey protein isolate enhance the thermal stability and slow the release of anthocyanins in simulated digestion and prepared instant coffee. (30th January 2021) - Wang, Shuo; Ye, Xinqi; Sun, Yue; Liang, Jin; Yue, Pengxiang; Gao, Xueling
Graphical abstract: Highlights: Encapsulation of anthocyanins in whey protein and polysaccharides (CHC and CMC). Intermolecular interactions occurred among ACNs, polysaccharides and proteins. Encapsulation improved stability and delayed release of ACNs. Encapsulated ACNs increased the antioxidant properties of a hot coffee beverage. Abstract: Anthocyanins (ACNs) are naturally derived colorants and antioxidants added to manufactured foods. ACNs were encapsulated in nanocomplexes with chitosan hydrochloride (CHC), carboxymethyl chitosan (CMC) and whey protein isolate (WPI). The ACN-loaded CHC/CMC-WPI nanocomplexes (ACN-CHC/CMC-WPI) showed a preferred particle size (332.20 nm) and zeta potential (+23.65 mV) and a high encapsulation efficiency (60.70%). ACN-CHC/CMC-WPI nanocomplexes exhibited a smooth spherical shape by transmission electron microscopy. Fourier transform infrared (FT-IR) and Raman spectroscopy confirmed interactions between the ACNs and the encapsulation materials (CHC/CMC-WPI). The nanocomplexes or the nanocomplexes incorporated into coffee beverage better protected ACNs at high temperature compared to the unencapsulated ACNs. In simulated gastrointestinal fluids, the ACNs in the ACN-CHC/CMC-WPI were more stable and more slower released over time. The nanocomplexes maintained high DPPH and hydroxyl free radical scavenging activities. This study indicated that CHC/CMC-WPI nanocomplexes can improve the thermal stability and slow the release of ACNs added to food products.